Possible paths towards sustainable tourism development in a high-mountain resort - Laurent Arcuset (Revue de Géographie Alpine)
This text starts from the teachings stemming from an evaluation of the tourist practices in the light of sustainable tourism principles, realized in 2004 within the framework of a national network piloted by the French Agency of Touristic Engineering (today ODIT France), for the ski resort of Valloire, first-generation resort in the Maurienne, which development and modernization in the 2000s kept pace with a vast real estate program. The article investigates the stakes and difficulties of the implementation of sustainable development in Valloire, asks the question of the "cultural revolution" which the actors should achieve to change the model of economic development, and suggest some tracks to reach there. The local approach of "sustainable tourism", indeed, seems for the moment rather to aim - as in many other high mountain ski resorts - towards a more environmental management of the basic urban functions than a real questioning of a tourist model based upon the triptych development of the ski slopes, securizing of the snow resource and touristic real estate programs.